Evolution of Reynolds Stresses in Turbulent Wake-Flows with Longitudinal Pressure Gradient - Elsner, J.W.; Wilczyński, J. (Engineering Transactions, 1976)
The report presented here deals with the theoretical as well as experimental analysis of the development of Reynolds stresses in shear flows with longitudinal pressure gradients. The obtained results have pointed out that the negative pressure gradient accelerates the mean velocity field equalization and damps the turbulent fluctuations of the flowing medium. The positive value of brings about the growth of the overall turbulence level which is probably due to an increase of energy-flux transferred from the mean to the turbulent motion. Special importance has also been attached to the analysis of energy spectrum functions and their dependence on longitudonal pressure gradient, The spectral coefficient of double correlation between turbulent velocity components has been found to be an increasing function of , which may be treated as a tendency of accelerated flows to a more intensive stabilization of isotropic structure.